Charge-driven interfacial gelation of cellulose nanofibrils across the water/oil interface. Issue 2 (13th November 2019) - Calabrese, Vincenzo; da Silva, Marcelo A.; Schmitt, Julien; Hossain, Kazi M. Zakir; Scott, Janet L.; Edler, Karen J.
Abstract : Interfacial gels, obtained by the interaction of water-dispersible oxidised cellulose nanofibrils (OCNF) and oil-soluble oleylamine (OA), were produced across water/oil (W/O) interfaces and studied using imaging and interfacial rheology. Abstract : Interfacial gels, obtained by the interaction of water-dispersible oxidised cellulose nanofibrils (OCNF) and oil-soluble oleylamine (OA), were produced across water/oil (W/O) interfaces. Surface rheology experiments showed that the complexation relies on the charge coupling between the negatively-charged OCNF and OA. Complexation across the W/O interface was found to be dependent on the ζ -potential of the OCNF (modulated by electrolyte addition), leading to different interfacial properties. Spontaneous OCNF adsorption at the W/O interface occurred for particles with ζ -potential more negative than −30 mV, resulting in the formation of interfacial gels; whilst for particles with ζ -potential of ca. −30 mV, spontaneous adsorption occurred, coupled with augmented interfibrillar interactions, yielding stronger and tougher interfacial gels. On the contrary, charge neutralisation of OCNF ( ζ -potential values more positive than −30 mV) did not allow spontaneous adsorption of OCNF at the W/O interface. In the case of favourable OCNF adsorption, the interfacial gel was found to embed oil-rich droplets – a spontaneous emulsification process.